Preconditions to parenthood: changes over time and generations. (August 2021) - Bodin, Maja; Holmström, Charlotta; Plantin, Lars; Schmidt, Lone; Ziebe, Søren; Elmerstig, Eva
Abstract: Reproductive decision-making and fertility patterns change with time and place, and are influenced by contemporary societal factors. In this paper, we have studied biosocial aspects of reproductive decision-making over time and generations in a Nordic setting. The aim was to explore intergenerational changes and influences on decision-making, especially regarding preconditions to first birth. Twenty-six focus group interviews were conducted in southern Sweden, including a total of 110 participants aged 17–90 years. The analysis of the interviews resulted in six themes: (i) 'Providing security – an intergenerational precondition'; (ii) 'A growing smorgasbord of choices and requirements'; (iii) 'Parenthood becoming a project'; (iv) 'Stretched out life stages'; (v) '(Im)possibilities to procreate'; and (vi) 'Intergenerational pronatalism'. Our findings reflect increasing expectations on what it means to be prepared for parenthood. Despite increasing awareness of the precariousness of romantic relationships, people still wish to build new families but try to be as prepared as possible for adverse events. The findings also show how increasing life expectancy and medical advancements have come to influence people's views on their reproductive timeline.